Family Ties from the Perspective of Property Division Deeds - Peres, Zsuzsanna (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The basic unit of Hungarian private law relations before 1848, especially from the point of view of the nobiliary private law, was not so much the individual as the family. Although the person who acquired the right could be the individual, the right over the property acquired by him usually extended beyond his person to other members of his family living in a blood relationship with him, to his relatives whom he had to divide his property, such as his (mainly male) children, brothers and sometimes sisters, and, where appropriate, to his more distant collateral relatives. This study attempts to present family law relations in the early modern Hungary through a special group of documents, the wills and property division deeds. The basis of the investigation in the present study are the wills and division deeds of some Hungarian noble families from the 17th-19th centuries, which played a decisive role in national politics, but due to the scope of the study these are only arbitrarily selected, without aiming for completeness.